Treatment of telomeropathies. Issue 2 (June 2021) - Vieri, Margherita; Brümmendorf, Tim H.; Beier, Fabian
Abstract: Telomeropathies or telomere biology disorders (TBDs) are a group of rare diseases characterised by altered telomere maintenance. Most patients with TBDs show pathogenic variants of genes that encode factors involved in the prevention of telomere shortening. Particularly in adults, TBDs mostly present themselves with heterogeneous clinical features that often include bone marrow failure, hepatopathies, interstitial lung disease and other organ sites. Different degrees of severity are also observed among patients with TBDs, ranging from very severe syndromes manifesting themselves in early childhood, such as Revesz syndrome, Hoyeraal-Hreidarsson syndrome, and Coats plus disease, to dyskeratosis congenita (DKC) and adult-onset "cryptic" forms of TBD, which often affect fewer organ systems. Overall, the most relevant clinical complications of TBD are bone marrow failure, lung fibrosis, and liver cirrhosis. In this review, we summarise recent advances in the management and treatment of TBD and provide a brief overview of the various treatment approaches.